Study of the Dance Heritage Map elaborated by the CDAEM - Santamaría Jiménez, Alicia (Revista General de Información y Documentación, 2024)
The Dance Heritage Map drawn up by the CDAEM brings together a selection of institutions which conserve dance-related heritage. Based on this database, updated in 2021, a statistical study was carried out by means of questionnaires sent to the different institutions to obtain a more detailed picture of their situation. The questionnaires were validated by the expert judgement method and the study lasted from 2019 to 2023. The analysis of the results showed the difficult situation of some centres with a marked lack of staff, space or technical and financial resources. Other strong points of the study were, on the one hand, the establishment of a documentary typology within dance, with the surveys coinciding with the one initially proposed and recommended by the selection of experts. On the other hand, it is noteworthy that a considerably high percentage of institutions indicated that they organise live dance activities, with the consequent added value that this discipline can bring to a such a cultural institution.
Keywords: heritage; dance; map; institutions; study; Spain; conservation